Subjugated Knowledges - Brake, Laurel. author. aut Link
XVIII, 228 p.
Keywords: Examining the relation of print and culture in the 19th century, this book scrutinizes the cultural politics and production of Victorian magazines. A high degree of interdependence among literature, history and journalism is alleged, and ways in which space is designated male or female is explored.